Narration and argumentation in the Historia índica (1572) by Pedro Sarmiento de Gamboa - González Díaz, Soledad Carmina; Zuleta Carrandi, Joaquín (Universidad Católica del Norte, Instituto de Investigaciones Arqueológicas y Museo, 2019)
This article analyzes how Pedro Sarmiento de Gamboa wrote the text of the Historia índica, which aimed to set the basis of the political program of Viceroy Francisco de Toledo in the Andes. Sarmiento’s argumentation uphold an historic interpretation that seeks to get rid of any doubt about the legitimacy of the Spanish conquest, under the assumption that the Incas had been tyrannical rulers of Peru. This proposal is centered in four principal ideas: personal benefit of its rulers, natural law transgression, illegitimate succession and prescription’s impossibility of its dominance. Starting from the text and manuscript analysis, we give an account of the phases involved in its composition process and we contribute with new points of view about the polemic certification of the chronicle in front of royal Inca ayllus.